Leiopus taeniatus (Gmelin, 1790) (Coleoptera, Cerambycidae) – a misidentified species and forgotten name - Kvamme, Torstein; Wallin, Henrik; Sörensson, Mikael (Norwegian Journal of Entomology, 2024)
This study shows that Leiopus taeniatus (Gmelin, 1790) (Coleoptera, Cerambycidae) is not a junior subjective synonym of Leiopus nebulosus (Linnaeus, 1758) but a senior subjective synonym of Leiopus punctulatus (Paykull, 1800), as revealed by Ivan I. Lepyokhin’s (Lepechin’s) original diagnosis and illustration of an unnamed “Cerambyx” beetle in his 1768–1772 expedition itinerary, subsequently adopted and explicitly named as Cerambyx (Stenocorus) taeniatus in Gmelin (1790) and here re-interpreted. No type or any other specimens from before 1900 labelled as L. taeniatus has been found and the type is considered lost. We consider Leiopus taeniatus a forgotten name (nomen oblitum) and invalid since it has not been used as valid after 1899. Consequently, its junior synonym Leiopus punctulatus (Paykull, 1800) should be considered the valid name and, accordingly, a nomen protectum. Both L. taeniatus (Gmelin, 1790) synonymum novum and its senior objective synonym L. bifasciatus (Goeze, 1777) (invalid homonym) should be listed under L. punctulatus (Paykull, 1800) as invalid synonyms and Leiopus linnei Wallin, Nylander & Kvamme, 2009 resurrected as a valid name.
Keywords: Cerambycidae; Coleoptera; Leiopus; Lepechin; Lepyokhin; linnei; nebulosus; new synonym; nomen oblitum; nomen protectum; nomenclature; punctulatus; resurrection of name; taeniatus; taxonomy